Development of a Learning Enrichment Material in Morphology: A Focus on Word Formation Processes - Ramos, Angelou O. (Asian Journal of Multidisciplinary Studies, 2020)
There has been abundant research on vocabulary learning, but the bottom line is that in order for a word to be learned incidentally or intentionally, a learner must attain access to the word’s form and meaning. Language learning is a time-consuming and complicated process composed of many individual skills and processes. Among these processes is vocabulary acquisition, an essential step in reaching the status of fluent speaker. This study sought to develop a learning enrichment material in morphology to college students. Specifically, it was focused on word formation processes as the 93 Education English major students were already grammatically competent on the use of derivational and inflectional morphemes with relative to the findings of the studies entitled “On Derivational Morphemes: Grammatical Competence of College Students” and On Inflectional Morphemes: Grammatical Competence of College Students” respectively. The descriptive survey method was utilized as the research described and attempted to interpret how the overall level of grammatical competence on derivational and inflectional morphemes of Education English major students differ when categorized in terms of demographic characteristics. Survey and written test questionnaires were utilized as instruments of this study on which findings showed that most of the college students were found to have high grammatical competence on derivational and inflectional morphemes. Hence, the development of a learning enrichment material focused on word formation processes was deemed necessary.